Pump it up : the heart and blood - Randolph, Joanne (Amazing human body (Enslow Publishing), 2018)
Explores the human heart and its functions, discussing the importance of oxygen, the work blood does, and current scientific experimentation on blood. Includes color photographs, a glossary, and further resources.